Psychological Empowerment and Performance of Millennials and Generation Z Employees in the IT Sector: Mediating Role of Affective Commitment (Quest Journal of Management and Social Sciences, 2025)
Background: In today's technologically advanced and competitive workplace, employee performance has grown more important, particularly as Gen Z and millennials change workplace expectations with stronger desires for autonomy, flexibility, and meaningful work. Understanding how psychological empowerment enhances performance and emotional commitment among younger workforce cohorts is crucial for improving motivation, retention, and long-term organizational sustainability in the rapidly expanding IT sector.Purpose: This study examines the influence of psychological empowerment dimensions (meaning, competence, self-determination, and impact) on the performance of millennials and Gen Z employees in Nepal's IT sector, and how affective commitment mediates these relationships within the dual theoretical perspectives of self-determination and social exchange theories. Design/methodology/approach: Purposively, cross-sectional data were collected from 270 millennials and Gen Z employees involved in technical roles and remote work roles. The structural path was examined using SmartPLS 4.0v.Findings: The descriptive findings demonstrated moderate levels of empowerment and intrinsic motivators as key drivers of performance and emotional attachment in digitally enabled work settings. All the dimensions of psychological empowerment showed significant influence on employee performance, with impact emerging as the most dominant factor and self-determination exerting the least influence. Similarly, affective commitment mediated the relationship between all four dimensions of psychological empowerment and performance.Conclusion: The findings highlight that psychological empowerment serves as a psycho-relational process that converts intrinsic motivation into affective reciprocity, providing multi-level implications for promoting an empowered, emotionally resilient, and high-performing workforce. This study highlights the significance of employees feeling psychologically empowered and emotionally connected in fostering long-term relationships with the organization.Keywords: Affective commitment, employee performance, Generation Z, Millennials, psychological empowerment